2012
DOI: 10.1136/emermed-2011-201000
|View full text |Cite
|
Sign up to set email alerts
|

Preventive behaviours against radiation and related factors among general workers after Fukushima's nuclear disasters

Abstract: These results provide information that may help with the targeting of health information after a nuclear disaster. This may contribute to determining an order of priority when distributing information after a nuclear disaster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Details of the study have been published previously 17. The study targets were participants who took part in one or more health seminars hosted by or conducted under the joint auspices of the Fukushima Occupational Health Promotion Center (FOHPC) between June and August 2011.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the study have been published previously 17. The study targets were participants who took part in one or more health seminars hosted by or conducted under the joint auspices of the Fukushima Occupational Health Promotion Center (FOHPC) between June and August 2011.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a previous study reported that many residents have evacuated from Fukushima Prefecture on account of anxiety over radiation exposure 13 ) . From the perspective of mental health, the association between anxiety over radiation exposure and other relevant factors has yet to be clarified, while past studies on radiation protection of general workers in Fukushima Prefecture indicated an association between the workers' behavioral aspects and the age groups of their children 14,15) .…”
Section: Introductionmentioning
confidence: 99%
“…Changing their lifestyle had negative impacts on their finances and health. To prevent radiation exposure, many parents who did not chose voluntary evacuation encouraged their children to wash their hands and gargle frequently, and refrained from going outside (Kanda, Hayakawa, & Koyama, ). In addition, the radiation issue became taboo among the people of Fukushima, because they feared conflict in perceptions of radiation risk among community residents, and therefore, hid their anxiety (Murakami et al, ).…”
Section: Discussionmentioning
confidence: 99%